Exploring the Lean Phenotype of Glutathione-Depleted Mice: Thiol, Amino Acid and Fatty Acid Profiles. - Amany K Elshorbagy; Fredrik Jernerén; Cheryl L Scudamore; Fiona McMurray; Heather Cater; Tertius Hough; Roger Cox; Helga Refsum (PLoS ONE)
Background Although reduced glutathione (rGSH) is decreased in obese mice and humans, block of GSH synthesis by buthionine sulfoximine (BSO) results in a lean, insulin-sensitive phenotype. Data is lacking about the effect of BSO on GSH precursors, cysteine and glutamate. Plasma total cysteine (tCys) is positively associated with stearoyl-coenzyme A desaturase (SCD) activity and adiposity in humans and animal models. Objective To explore the phenotype, amino acid and fatty acid profiles in BSO-treated mice. Design Male C3H/HeH mice aged 11 weeks were fed a high-fat diet with or without BSO in drinking water (30 mmol/L) for 8 weeks. Amino acid and fatty acid changes were assessed, as well as food consumption, energy expenditure, locomotor activity, body composition and liver vacuolation (steatosis). Results Despite higher food intake, BSO decreased particularly fat mass but also lean mass (both P<0.001), and prevented fatty liver vacuolation. Physical activity increased during the dark phase. BSO decreased plasma free fatty acids and enhanced insulin sensitivity. BSO did not alter liver rGSH, but decreased plasma total GSH (tGSH) and rGSH (by ~70%), and liver tGSH (by 82%). Glutamate accumulated in plasma and liver. Urine excretion of cysteine and its precursors was increased by BSO. tCys, rCys and cystine decreased in plasma (by 23-45%, P<0.001 for all), but were maintained in liver, at the expense of decreased taurine. Free and total plasma concentrations of the SCD products, oleic and palmitoleic acids were decreased (by 27-38%, P <0.001 for all). Conclusion Counterintuitively, block of GSH synthesis decreases circulating tCys, raising the question of whether the BSO-induced obesity-resistance is linked to cysteine depletion. Cysteine-supplementation of BSO-treated mice is warranted to dissect the effects of cysteine and GSH depletion on energy metabolism.